An Introduction to Network Programming with Java - Graba, Jan. (Springer London : Imprint: Springer, 2007)
The continually expanding popularity of both the Internet and local intranets means that the ability to construct reliable network software is a vital skill for many of today's programmers. At the same time, Java's comprehensive libraries of readily-accessible network programming features ensure that Java remains at the forefront of network software development. The first edition of An Introduction to Network Programming with Java provided a 'streamlined' work that could serve equally well as the core text on an undergraduate module and as the quick, clear, 'no-nonsense' guide required by a busy IT professional. Notable amongst its features were its numerous code examples, screenshots and end-of-chapter exercises. The second edition retains these features, but builds upon the success of the original text by introducing the following changes and additions: • Language changes throughout the examples (and the model solutions on the Web site), largely reflecting the significant changes introduced by J2SE 5.0; • Comprehensive update of support software, particularly that used for Web applications; • New material, such as non-blocking servers and the use of the DataSource interface and Data Access Objects (DAOs) for connecting to remote databases; Jan Graba is a Senior Lecturer in Software Engineering at Sheffield Hallam University, where he has specialised in the teaching of network programming with Java for the past five years.